2020
DOI: 10.1371/journal.pone.0242244
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopment of HIV-exposed uninfected children in Cape Town, South Africa

Abstract: Background Evidence shows that antiretroviral (ART) exposure is associated with neurodevelopmental delays in human immunodeficiency virus (HIV)-exposed uninfected (HEU) children. However, there are few insights into modifiable maternal and child factors that may play a role in improving neurodevelopment in HEU children. We used a parent-centric neurodevelopment tool, Ages & Stages Questionnaire (ASQ) to examined neurodevelopment in HEU children at 12–24 months of age, and associations with maternal and chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…There was high variability in sample sizes, ranging from 54 to 6573. The studies were conducted across ten sub-Saharan African countries, but most were done in South Africa [ 23 , 27 , 29 , 30 , 31 , 34 , 36 ]. Three studies were multicentred, pooling data from Uganda and Burkina Faso [ 39 ], Uganda and Malawi [ 24 ], and Ghana and Malawi [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There was high variability in sample sizes, ranging from 54 to 6573. The studies were conducted across ten sub-Saharan African countries, but most were done in South Africa [ 23 , 27 , 29 , 30 , 31 , 34 , 36 ]. Three studies were multicentred, pooling data from Uganda and Burkina Faso [ 39 ], Uganda and Malawi [ 24 ], and Ghana and Malawi [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 17 studies on cognitive development, 12 were prospective cohort studies [23][24][25][26][27][28][29][30][31][32][33][34], four were cross-sectional studies [35][36][37][38], and one was a cluster RCT [39] (Table 1 and Table S3 in the Online Supplementary Document). These studies were published between 2013 and 2021, with the majority (88%) published in the last five years.…”
Section: Breastfeeding and Cognitive Development In Sub-saharan Africamentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically in Southern Africa, three studies, one each from South Africa ( Wedderburn et al, 2019b ), Botswana ( Chaudhury et al, 2017 ) and Zimbabwe ( Ntozini et al, 2020 ), reported language delay in HEU infants and children; two studies, one in South Africa ( Le Roux et al, 2018 ) and one in Zimbabwe ( Ntozini et al, 2020 ), poorer motor development; and one study ( Springer et al, 2012 ) poorer adaptive behavior. Another study performed in South Africa found delayed gross and fine motor development (that was independent of ART initiation timing) in a higher proportion of HEU infants at age 12–24 months than typically seen in unexposed infants from similar communities ( Madlala et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, investigations of these effects are often hampered by the lack of representative HIV-unexposed controls. In addition to negative associations with survival [8], growth [7] and cognitive development [9], several observational studies have described cardiac changes from early life stages in HEU children [10,11]. We have previously reported structural and functional cardiac changes in utero of Spanish HEU infants, mainly related to maternal zidovudine-containing ART regimens [12,13].…”
Section: Introductionmentioning
confidence: 99%